Social protection, electoral competition, and political branding in Malawi - Sam Hamer; Jeremy Seekings (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2017)
Competitive elections in many parts of Africa generate powerful incentives to presidential candidates (and to a lesser extent political parties) to brand themselves in ways that transcend regional or ethnic loyalties. In Malawi, Joyce Banda - President from 2012 to 2014 - sought to distinguish herself from her competitors by branding herself and her new People's Party as the champions of social protection for women, children, and the poor. Some of the conditions that favoured Banda's adoption of a social protection brand were specific to the political context in Malawi. Elsewhere in East and Southern Africa, presidential candidates and parties have generally denounced 'handouts' and avoided the social protection brand. In practice, her rhetorical embrace of social protection and 'handouts' was not matched by delivery during her two years in office. Banda's defeat in the 2014 Malawi election, although caused partly by other factors, suggests that there are limits to the efficacy of social protection branding. Nonetheless, the fact that she has used this brand at all suggests that social protection has grown in political significance, as an expression of pro-poor priorities.
Keywords: I38; O29; O21; O57; 330; elections; political branding; social protection; poverty alleviation; Joyce Banda; Malawi; social spending